Multimodal cardiac imaging and endoscopic ultrasound-guided fine needle aspiration for accurate diagnosis and management of giant primary pericardial schwannoma: a case report with literature review - Konuş, Ali Hakan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPrimary pericardial schwannoma is a highly unusual tumor, and only a few cases have been reported in the literature. We report a case of giant primary pericardial schwannoma that was accurately diagnosed and managed by multimodal cardiac imaging and transesophageal endoscopic ultrasound-guided fine needle aspiration (EUS-FNA).CaseA 47-year-old female patient presented with complaints of exertional dyspnea and non-anginal chest pain. The patient's New York Heart Association (NYHA) functional capacity score was 2–3 and N-terminus pro-B type natriuretic peptide (NT-proBNP) was elevated at 684 pg/ml. Transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE) revealed a well-circumscribed mass containing a cystic lesion, compressing the left atrium (LA) and inferior vena cava (IVC). Thoracic computed tomography (CT) angiography revealed that the lesion was intrapericardial, located in the posterior mediastinum, 10.1 cm × 8.1 cm × 5.2 cm in size, had regular borders, and was compressing the esophagus. Magnetic resonance imaging (MRI) showed a well-circumscribed, T1-hypointense and T2-hyperintense pericardial mass. The mass was observed to have homogeneous signal intensity on T1 and T2-weighted images. CT and MRI showed that the mass did not cause myocardial involvement. Whole-body 18 F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)-CT images revealed that the mass was primary, had no metastasis, and had mild to moderate 18F-FDG avidity. Immunohistochemical evaluation with EUS-FNA determined the mass to be consistent with schwannoma, and the Ki-67 index was less than 1%. The mass was completely removed after the pericardium was opened by performing a median sternotomy approach. No residual mass was detected in the patient's follow-up. At 6-month and 1-year follow-ups, there were no symptoms, the NYHA score was 1, and NT-proBNP was normal.ConclusionThe integrative approach of multimodal cardiac imaging and EUS-FNA can effectively guide the surgical approach and management of primary pericardial schwannomas preoperatively. EUS-FNA may be an effective and safe method in the management of cardiac schwannomas. To our knowledge, this is the first case in which EUS-FNA has been used for the diagnosis of cardiac schwannoma.